Social ties and sustainability in neighborhood canteens: A care-based approach - Dyen, Margot; Michaud, Maxime (Frontiers in Sustainability, 2023)
Introduction This article proposes to study the mechanisms by which food, and particularly commensality, generates social ties. Methods It mobilizes the conceptual framework of care, and is based on a qualitative methodology inspired by ethnography, to study neighborhood canteens. Two non-profit organizations were investigated, both having in common the willing to generate social ties between people living or working in the same neighborhood through the sharing of meals. We conducted participant observations and two sets of semi-structured interviews with stakeholders of the structure, either managers, employees or members. The first series aimed at describing the experiences of the participants and their sociocultural background. The second series used the projective method of collages, in order to go deeper in the understanding of the relationships between the members and with the structures. Results The results show that there are different postures toward neighborhood canteens, between a desire to receive care and a desire to give care. Discussion We thus identify that the search for care is based on the need for recognition, valorization and reassurance and that the kind of social ties created and experienced by the stakeholders is highly dependent on the compatibility of their expectations regarding care.